Rectus muscle excyclorotation and V-pattern strabismus: a quantitative appraisal of clinical relevance in syndromic craniosynostosis. Issue 11 (20th March 2017) - Dagi, Linda R; MacKinnon, Sarah; Zurakowski, David; Prabhu, Sanjay P
Abstract : Purpose: V-pattern strabismus observed with syndromic craniosynostosis has been attributed to disparate causes. We compared severity of V pattern with degree of excyclorotation of rectus muscles to appraise significance of this proposed aetiology. Methods: 43 patients with Apert, Crouzon or Pfeiffer syndrome referred to Boston Children's Hospital Department of Ophthalmology were identified. 28 met inclusion criteria for retrospective cohort study, specifically: (1) sensorimotor measurements in minimum of seven cardinal gazes, (2) quantified fundus torsion and (3) orbital CT imaging sufficient to measure rectus muscle cyclorotation in coronal and quasicoronal planes, posteriorly (near orbital apex) and anteriorly (near pulleys). Patients were placed in one of four V-pattern severity groups. The most severe group demonstrated inability to elevate abducted eye above midline with characteristic 'seesaw' misalignment during horizontal saccades. Rectus muscle cyclorotation was measured by paediatric neuroradiologist blinded to group placement. Primary outcome was correlation of severity of V pattern with degree of excyclorotation. Secondary outcome was correlation of severity with craniosynostosis syndrome. Results: Increasing severity of V pattern correlated with greater excyclorotation in anterior coronal (p=0.009), anterior quasicoronal (p=0.021), posterior coronal (p=0.014) and posterior quasicoronal (p=0.040) planes for moderate-to-severe V pattern. Even greater excyclorotation was associated with seesaw V pattern in anterior quasicoronal (p=0.004) and posterior quasicoronal (p=0.001) views. Highly significant association was found between Apert syndrome and severity of V pattern (p=0.004). Conclusions: Severity of V pattern is associated with magnitude of excyclorotation. More severe V pattern and seesaw strabismus noted with Apert syndrome may relate to distinctive orbital morphology.